Starting school : a guide for parents and caregivers - Renwick, Margery, 1935- (Wellington [N.Z.] : New Zealand Council for Educational Research, 1997)
Starting school. The early years. Be positive. Choosing a school. Integrated and independent schools. Enrolment policies...
Keywords: Education; Primary Education; Educational entrants; Readiness for school; New entrants (Education) -- New Zealand; Readiness for school -- New Zealand; Education, Primary -- New Zealand